2017
DOI: 10.1080/09712119.2016.1276916
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ruminal dry matter and crude protein degradability and degradation kinetics of several concentrate feed ingredients in cashmere goat

Abstract: The objective of this study was to determine the dry matter (DM) and crude protein (CP) degradation parameters of several commercially available concentrate feed ingredients used in Shaanbei White Cashmere Goat (SWCG). Three 4-year-old female SWCGs fitted with permanent rumen fistula were fed with corn straw and concentrate feed. Tested energy and protein feed ingredients were corn, wheat bran (WB), corn germ meal, soybean meal (SBM), rape seed meal (RSM), and distillers dried grains. The feed samples were pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Inner Mongolia Cashmere goats are excellent variety, which can offer cashmere and meat. Now, the research on Cashmere goat is mainly focused on cashmere performance, rumen metabolism, and nutritional metabolism (Ansari‐Renani et al., 2011; Bai et al., 2017; Lei et al., 2017). However, the antioxidant properties of cashmere goats are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inner Mongolia Cashmere goats are excellent variety, which can offer cashmere and meat. Now, the research on Cashmere goat is mainly focused on cashmere performance, rumen metabolism, and nutritional metabolism (Ansari‐Renani et al., 2011; Bai et al., 2017; Lei et al., 2017). However, the antioxidant properties of cashmere goats are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…nutritional metabolism (Ansari-Renani et al, 2011;Bai et al, 2017;Lei et al, 2017). However, the antioxidant properties of cashmere goats are rarely studied.…”
mentioning
confidence: 99%
“…The dry matter digestibility of a rice straw diet supplemented with SBM for goats was 59.5% [4]. In addition, the degradability of SBM, using an in situ technique, in Cashmere goats after incubation for 12 and 24 h was approximately 64.75 and 80.57% of the dry matter, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…As described in a preceding study (Musco et al, 2017), the carbohydrate fractions affect the kinetics of fermentation differently: starch promotes a more intense and rapid process, while structural carbohydrates trigger a slower and less stable fermentation. Lei et al (2018) reported that the dry matter degradability of feed ingredients in rumen increased with increasing incubation time, the degradation of energy feed ingredients was on an uptrend prior to 24 h incubation and then the process slowed down, while protein feed ingredients were at 36 h, which was on an uptrend all the time. This suggested that feed ingredients for energy feed ingredients were almost entirely digested at 24 h and 36 h for protein feed ingredients, respectively.…”
Section: Resultsmentioning
confidence: 99%